13x^(2)+41x ( до подставления )
-240 ( с подставлением )
Объяснение:
Упростить
(3х – 4)² + (2x – 4)(2х + 4) + 65х = 9x^(2) - 24x + 4x^(2) + 65x = 13x^(2) + 41x
Подставляем
13 * (-3^(2)) + 41 * (-3) = - 13 * 3^(2) - 41 * 3 = 3(-13 * 3 - 41) = 3*(-80) = - 240
13x^(2)+41x ( до подставления )
-240 ( с подставлением )
Объяснение:
Упростить
(3х – 4)² + (2x – 4)(2х + 4) + 65х = 9x^(2) - 24x + 4x^(2) + 65x = 13x^(2) + 41x
Подставляем
13 * (-3^(2)) + 41 * (-3) = - 13 * 3^(2) - 41 * 3 = 3(-13 * 3 - 41) = 3*(-80) = - 240